2022
DOI: 10.1111/cts.13430
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of complications from indwelling pleural catheter for pleural effusion: A meta‐analysis

Abstract: Indwelling pleural catheter (IPC) is widely used in patients with pleural effusion (PE). This meta‐analysis aimed to comprehensively summarize the clinical complication from IPC. We searched four large electronic databases (PubMed, EMBASE, MEDLINE, and Cochrane Library) for potentially relevant studies and assessed the included studies’ quality using the methodological index for nonrandomized studies’ criteria. Extracted data were used to pool rates, and to conduct subgroup and meta–regression analyses. Forty‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…40 Previous meta-analyses found blockage rates between 1.5 and 3.7% and leakage rates of approximately 0.6%. 9 13 Other studies have reported blockage rates up to 18.1% and leakage up to 2%. 40 41 Not surprisingly, these rates are higher if the IPC remains longer in situ.…”
Section: Common Indwelling Pleural Catheter Complicationsmentioning
confidence: 96%
See 3 more Smart Citations
“…40 Previous meta-analyses found blockage rates between 1.5 and 3.7% and leakage rates of approximately 0.6%. 9 13 Other studies have reported blockage rates up to 18.1% and leakage up to 2%. 40 41 Not surprisingly, these rates are higher if the IPC remains longer in situ.…”
Section: Common Indwelling Pleural Catheter Complicationsmentioning
confidence: 96%
“…Aforementioned meta-analyses found dislodgement rates of 2.2%. 9 13 Other series reported a wide range of incidence rates between 1.2 and 18%. 24 40 41 Once again, the incidence was greater in those with longer follow-up period, which had a rate of up to 33.3%.…”
Section: Less Common Indwelling Pleural Catheter Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 IPC-related infections develop in up to 12% of the cases. 47,48 In the only randomized trial on 68 refractory transudative PEs (46 with HF), where 21 HF patients were assigned to the IPC group and 25 to the TT group, the mean daily breathlessness score over 12 weeks from randomization was not significantly different in both branches. 49 More nonserious adverse events were noted in the IPC group (59 vs. 37%).…”
Section: Interventional Proceduresmentioning
confidence: 98%